Human as Relational: A Study in Critical Ontology - Neelamkavil, Raphael` (Journal of Dharma, 2003)
Joseph Kaipayil, Human as Relational: A Study in Critical Ontology, Gottigere, Bangalore: Jeevalaya Institute of Philosophy, 2003, pages xii + 62, ISBN 81-87664-03-7.